A research on machining parameters during dry machining of Ti-6Al- 4V alloy. (2021) - Samsudeensadham, S.; Mohan, A.; Krishnaraj, V.
Abstract: Aerospace structural components made of titanium alloy (Ti6Al4V) material requires end milling operations to achieve the required tolerance limits. Selection of optimal machining parameters to attain the desired surface quality and better tool life are the most critical task during finish machining of titanium alloys at dry machining conditions. Usually dry machining generates a very high cutting temperature and cutting force (feed force and tangential force) which affects the surface quality and tool life. In this research investigation, the effect of feed rate and depth of cut on cutting forces, temperature and surface roughness were analyzed during the machining of Ti6Al4V work-piece material. The experiments were carried out under dry machining conditions based on full factorial design with a milling tool named 3 fluted tungsten carbide end mill cutter coated with TiN. The selected feed rates for the experiments are 0.03, 0.06, 0.09 and 0.12 mm/rev and the depth of cut are 0.5, 0.75, 1 and 1.25 mm with a constant cutting speed of 40 m/min. By from the machining research it was found that feed of 0.06 mm/tooth and depth of cut of 0.75 can be chose for machining of titanium alloy. The cutting force was found by using peak and valley points acquired from the dynamometer for the postulated machining time. Moreover, it is observed that feed rate has the higher influence on cutting force and temperature when compared to depth of cut.